Ambient Availability of Amino Acids, Proteins, and Iron Impacts Copper Resistance of Aspergillus fumigatus - Yap, Annie; Talasz, Heribert; Lindner, Herbert; Würzner, Reinhard; Haas, Hubertus (Frontiers in Cellular and Infection Microbiology, 2022)
The transition metals iron and copper are required by virtually all organisms but are toxic in excess. Acquisition of both metals and resistance to copper excess have previously been shown to be important for virulence of the most common airborne human mold pathogen, Aspergillus fumigatus. Here we demonstrate that the ambient availability of amino acids and proteins increases the copper resistance of A. fumigatus wild type and particularly of the ΔcrpA mutant that lacks export-mediated copper detoxification. The highest-protecting activity was found for L-histidine followed by L-asparagine, L-aspartate, L-serine, L-threonine, and L-tyrosine. Other amino acids and proteins also displayed significant but lower protection. The protecting activity of non-proteinogenic D-histidine, L-histidine-mediated growth inhibition in the absence of high-affinity copper uptake, determination of cellular metal contents, and expression analysis of copper-regulated genes suggested that histidine inhibits low-affinity but not high-affinity copper acquisition by extracellular copper complexation. An increase in the cellular copper content was found to be accompanied by an increase in the iron content, and, in agreement, iron starvation increased copper susceptibility, which underlines the importance of cellular metal balancing. Due to the role of iron and copper in nutritional immunity, these findings are likely to play an important role in the host niche.